Spatial Characterization of Arsenic, Cadmium, and Lead Concentrations in Tobacco Leaves and Soil. (2nd July 2016) - Lin, Beisen; Gao, Huajun; Lai, Hongmin
ABSTRACT: Metal accumulation in tobacco may have negative environmental and health impacts. The concentrations of arsenic, cadmium, and lead were determined in 300 tobacco plants by inductively coupled plasma–mass spectrometry. The plant-available concentrations of metals in the soil were measured. The metal concentrations in tobacco leaves were dependent on the variety of plant. The concentrations of arsenic and lead in leaves decreased in higher positions compared to lower locations, whereas cadmium showed the opposite trend. The accumulation of metals in leaves increased with the concentrations of plant-available and total metals in the soil. The leaf concentrations were also affected by the soil pH, electrical conductivity, and organic matter.